ROLE PLAYING AS TECHNIQUE FOR TEACHING SPEAKING TO HELP DEVELOPING THE STUDENTS’ CHARACTER - Arifah, Kurnia Fitri; Santosa, Riyadi; Ngadiso, Ngadiso (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2018)
Teaching speaking gives opportunity to provide fluency practice for language learners. The students can practice to speak by role playing as one of techniques in teaching speaking. However, students with the high speaking ability are worthless without good morals. For this reason, today the teacher has responsibility towards the student?s character. Unfortunately, the character building for students cannot be taught in isolation because it is not included in language skills. Therefore, the character building should be infused to the teaching learning process. This paper addresses the issue of role play as a technique in teaching speaking and developing students? character.